Automatic control - Djaferis, Theodore Euclid (Brooks/Cole Pub, 2000)
Includes bibliographical references (p. 141) and index.; This unique, brief, interdisciplinary text uses the concept of automatic control as a unifying idea to explain the field of engineering - and the kinds of problems engineers solve - to first-year students. The author focuses on the basic principle of feedback and shows how it is used to design automatic controllers. Students learn how to develop explicit engineering models, expressed as linear differential equations with constant coefficients for each of the systems they study. Then, they will learn to solve these equations both analytically and numerically. Numerical solutions are performed using SIMULINK. System stability and system performance are introduced, and the book concludes with a capstone project in which students use simulations and experiments to develop automatic controllers for a computer-controlled model car